(untitled) - Gordon, I. (Oxon, UK, 2003)
Cattle oocyte recovery and maturation, in vitro fertilization and embryo cryopreservation and transfer are techniques that permit cows to produce calves of a genetic quality and composition quite unlike that of the surrogate mother herself. The same techniques are also basic to progress in cattle cloning and the production of transgenes. The new edition of this book reviews advances in embryo production technology, based on some 3500 reports that have appeared since the first edition was published in 1994. The work emphasizes the common ground existing between those working in cattle and human embryology and the opportunities for gaining new knowledge and a greater understanding of the reproductive processes in the two species.
Keywords: Livestock,Livestock,Chăn nuôi,Chăn nuôi; Embryos,Embryos,Transplantation,Phôi,Phôi,Cấy